Modal analysis of dielectric loaded coaxial probe fed circular waveguide radiator - Safavi-Naini, S.; Ameri Mahabadi, H. (1991)
An almost rigorous procedure for analyzing dielectric resonator antennas in cylindrical enclosures is presented. The resonant frequency and radiation pattern of a circular waveguide radiator have been analyzed by the method presented. The primary consideration in this special design has been the bandwidth. Experimental results and theoretical predictions for two cases (∈=4,12) are shown. As is evident from this comparison, the method has a reasonable accuracy. In both cases, a piecewise sinusoidal distribution for the probe current has been assumed. In general a limited number of modes in both inhomogeneous and homogeneous regions provides sufficiently accurate results for many practical cases